Making intubation and extubation safe in the Covid era - Chong, Kok Wah; Azahar, Aizad (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
The highly infectious COVID-19 pandemic has in a way or the other affected everyone. Health care workers particularly anaesthesists who deal with airway manipulation are at an increased risk of being infected. Invasive procedures such as intubation and extubation performed mostly by anaesthetists are classified as procedures with high risk of aerosol generating particles where respiratory droplets containing the virus can easily spread to the surroundings. Various methods of preoxygenation, intubation and extubation have been further discussed and improvised with the aim of reducing the spread of aerosolization and making intubation safe. The purpose of this review is to identify the new techniques that are safe and effective in reducing aerosolization of respiratory droplets during the process of intubation and extubation. Anaesthetists are often not familiar with these new techniques and protocols. Thus far, no scientific data has been made available to support the superiority of each technique. Further research is needed to investigate each technique in the future.